Biomimetic Mineralized Organic–Inorganic Hybrid Macrofiber with Spider Silk‐Like Supertoughness. (27th November 2019) - Yu, Yadong; He, Yan; Mu, Zhao; Zhao, Yueqi; Kong, Kangren; Liu, Zhaoming; Tang, Ruikang
Abstract: Spider silk fibers (SSF) have a hierarchical structure composed of proteins with highly repetitive sequences and biomineralization is sophisticated in hierarchical organic–inorganic constructions. By using inorganic hydroxyapatite (HAP) and organic polyvinyl alcohol (PVA) to simulate the rigid crystalline and flexible amorphous protein blocks of SSF, respectively, biomimetic mineralization is herein attempted for the large‐scale preparation of SSF‐like macrofibers with a hierarchical ordered structure, a superhigh tensile strength of 949 ± 38 MPa, a specific toughness of 296 ± 12 J g −1, and a stretch ability of 80.6%. The hybrid macrofibers consist of microfibers, and their outstanding performance (e.g., extreme tolerance to temperatures ranging from −196 to 80 °C and superior ability to inhibit the transverse growth of cracks) is attributed to the hierarchical arrangement as well as the organic–inorganic integrated structure within the oriented mineralized polymer chains. The biomineralization‐inspired technique provides a promising tactic that can be used to synthesize functional organic–inorganic fibers that are structurally complex and, furthermore, industrially manufacture SSF‐like artificial fibers with a supertoughness. Abstract : Inspired by spider silk fibers (SSF) and biomineralization tactics, inorganic hydroxyapatite and organic polyvinyl alcohol are used to mimic the rigid crystalline structure and flexible amorphous domains of SSF, respectively, constructing supertough macrofibers with ordered mineralized polymer chain alignments, which yields a tensile strength of 949 ± 38 MPa, a specific toughness of 296 ± 12 J g −1, and a stretch ability of 80.6%.